A Patriot in Berlin - Read P. P. Piers Paul (London, Phoenix, 1996)
This is a novel about love, faith and patriotism, told from three different viewpoints: Andrei Orlov is the rogue KGB officer, art thief and murderer; Francesca McDermott is the art expert and Andrei's lover; and Gerasimov is the KBG officer given the job of tracking Orlov down.